Room Air Quality at Husada Prima Hospital, East Java Province - Sari Cahayaningtyas, Afifah Kartika; Khambali, Khambali; Sari, Ernita; Rachmaniyah, Rachmaniyah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
The microbiological quality of the air in the NICU and surgical rooms exceeds standards. The physical quality of the NICU and operating room exceeds the standard. This study aimed to determine the microbiological and physical quality of hospital room air (NICU room and surgical rooms) at Husada Prima Hospital, East Java Province. This research design was descriptive. Observation, field measurements, and laboratory tests collected data. The measurement results will be compared with RI Minister of Health Regulation No. 2 for 2023. The results of air microbiology sampling in the NICU, surgical room 1, and surgical room 2 still need to meet the requirements. The results of physical air quality measurements, namely temperature in the three rooms, humidity in the NICU room, lighting, and ventilation rate in the three rooms, must meet the requirements. The variables that meet the requirements are humidity in both operating rooms and lighting in the surgical room (Table 2). The condition of hospital facilities and buildings in the three rooms has met the requirements. The conclusion is that the room's air quality at Husada Prima Hospital, East Java Province, did not meet the criteria. The condition of the facilities and buildings was good. The hospital is advised to clean and repair air conditioners regularly, use humidifiers to maintain humidity in the room and increase or decrease lighting according to each room's needs.